2016
DOI: 10.1016/j.kint.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell–derived factor-1 is upregulated by dipeptidyl peptidase-4 inhibition and has protective roles in progressive diabetic nephropathy

Abstract: The role of stromal cell-derived factor-1 (SDF-1) in the pathogenesis of diabetic nephropathy and its modification by dipeptidyl peptidase-4 (DPP-4) inhibition are uncertain. Therefore, we studied this independent of glucagon-like peptide-1 receptor (GLP-1R) signaling using two Akita diabetic mouse models, the diabetic-resistant C57BL/6-Akita and diabetic-prone KK/Ta-Akita. Increased SDF-1 expression was found in glomerular podocytes and distal nephrons in the diabetic-prone mice, but not in kidneys from diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 57 publications
2
89
0
2
Order By: Relevance
“…These results showed that DPP-4 inhibition could have reno-protective effects through glucagonlike peptide-1 receptor (GLP-1R) and also through other substrates such as stromal derived factor-1 alpha (SDF-1a) independent of GLP-1R (Takashima et al 2016).…”
Section: Dpp-4 Inhibition In Animal Models Of Diabetic Nephropathymentioning
confidence: 98%
See 1 more Smart Citation
“…These results showed that DPP-4 inhibition could have reno-protective effects through glucagonlike peptide-1 receptor (GLP-1R) and also through other substrates such as stromal derived factor-1 alpha (SDF-1a) independent of GLP-1R (Takashima et al 2016).…”
Section: Dpp-4 Inhibition In Animal Models Of Diabetic Nephropathymentioning
confidence: 98%
“…These findings were counteracted with linagliptin treatment (Nistala et al 2014). Moreover, (Takashima et al 2016) used Glp1r -/-diabetic-prone Akita mice to show that linagliptin enhanced renal SDF-1 expression leading to improved renal outcomes, independent of GLP-1R signalling, which were counteracted using AMD3100, a selective SDF-1 receptor blocker. Thus the available data on SDF-1 in the setting of diabetic nephropathy remain controversial and need more investigation.…”
Section: Sdf-1amentioning
confidence: 99%
“…The administration of a GLP‐1 receptor agonist or a DPP‐4 inhibitor acts to attenuate the activity of NHE3 . However, the ability of DPP‐4 inhibitors to modulate NHE3 is not related to their action to prevent the degradation of GLP‐1; instead, DPP‐4 inhibitors appear to potentiate another endogenous natriuretic peptide that is degraded by DPP‐4 (potentially, stromal cell‐derived factor‐1) . This finding explains why the molecular pathways by which GLP‐1 receptor agonists and DPP‐4 inhibitors act to attenuate NHE3 activity are distinct; GLP‐1 receptor agonism exerts its effects on NHE3 through protein kinase A, whereas DPP‐4 inhibition acts through a tyrosine kinase pathway .…”
Section: Effect Of Drugs Used In Diabetes On the Sodium‐hydrogen Exchmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have verified that incretin agents, including DPP-4 inhibitors, exert renal protective effects against increased renal oxidative stress under hyperglycemic conditions via cAMP-PKA activation [37]; stromal cell-derived factor 1 upregulation and stromal cellderived factor 1-dependent anti-oxidative and anti-fibrotic effects on the diabetic kidney [38]; and inhibition of endothelialto-mesenchymal transition and renal fibrosis via suppression of endothelium DPP-4 and integrin β1 levels [39]. In clinical use, some pooled analysis and randomized controlled trials using DPP-4 inhibitors resulted in significant improvement of albuminuria [40,41].…”
Section: Effects Of Dpp-4 Inhibitors and Sglt2 Inhibitors On Glucose mentioning
confidence: 99%